Braking behaviour among motorcyclist: comparison of the rear brake using hand braking type and leg braking type / Mohammad Hamidi Sinin - Sinin, Mohammad Hamidi (2010)
Motor vehicle crashes have received considerable attention by Government. A Cabinet Committee on Road safety with the prime Minister as the chairman was later formed and target of reducing road fatalities by 30% by the year 2000 was set. Statistics shows more than half the motor vehicles in Malaysia are motorcycles and motorcycle crashed continue to be a problem in both developing and developed countries. Fatalities rates (measured in deaths per 10,000 registered vehicles) in crashed was much higher than in non motorcycle crashes. One of the common causes of crash is the braking characteristic of rider. Due to this project, an observation has been conduct to determine the characteristic of motorcycle rider during braking. The comparison between the rider using hand brake type and leg brake type has been considers. As the result the characteristic of motorcycle rider have been defined. The results have been comparing between the hand brake type and leg brake type motorcycle and then be analyze. The characteristic of rider have been evaluate and compared. Finally the conclusion has been made and some recommendation will be suggest.